The Jewish primer questions and answers on Jewish Faith and culture - Himelstein, Shmuel (Facts on File, 1990)
The Jewish Primer provides simple, forceful explanations of the faith and practices of Judaism. Reform and Conservative forms are briefly covered, but the work's emphasis is on traditional Orthodox beliefs. Himelstein offers succinct discussions of dietary laws, marriage and divorce, holy days, the Sabbath, sacred writings, Jewish life, and many other topics, all in question-and-answer format and supported by a subject index. This is an excellent introduction to the tenets of traditional Judaism.